2021
DOI: 10.3390/medicina57010033
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between PID-5 Personality Traits and Mental States. A Study on a Group of Young Adults at Risk of Psychotic Onset

Abstract: Background and Objectives: The diagnosis of psychosis is a challenge for the scientific community, both in terms of its definition and treatment. Some recent studies have investigated the relationship between personality and psychosis onset to prevent or intervene early. Materials and Methods: Sixty young adults were recruited during their first access in 2019 near the Community Mental Health Service of Niguarda Hospital, Milan, Italy. The assessment included the Social and Occupational Functioning Assessment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 47 publications
2
12
0
Order By: Relevance
“…Especially, the relationship between self-injurious behaviour and personality disorders has always been a topic of interest in literature, both in terms of prevention and effective treatment ( Meliante et al, 2021 ; Colle et al 2020 ; Urnes, 2009 ). The NSSI subgroup is notoriously associated with borderline personality disorder, as demonstrated by the presence of "self-injurious behaviour" among the DSM-5 diagnostic criteria ( Reichl and Kaess, 2021 ; APA, 2013; Krysinska et al 2006 ).…”
Section: Introductionmentioning
confidence: 99%
“…Especially, the relationship between self-injurious behaviour and personality disorders has always been a topic of interest in literature, both in terms of prevention and effective treatment ( Meliante et al, 2021 ; Colle et al 2020 ; Urnes, 2009 ). The NSSI subgroup is notoriously associated with borderline personality disorder, as demonstrated by the presence of "self-injurious behaviour" among the DSM-5 diagnostic criteria ( Reichl and Kaess, 2021 ; APA, 2013; Krysinska et al 2006 ).…”
Section: Introductionmentioning
confidence: 99%
“…Even though these aspects have already been investigated and discussed, the PID-5 has the potential to be used in research and clinical settings, to favor the advancement of knowledge regarding personality disorders, and support the characterization of psychopathologies, screening potential cases, and assessing the progression of treatments ( 23 26 ). In this context, it is noteworthy that its psychometric properties have not been assessed for the Brazilian context; thus far, our research group has conducted its translation and cross-cultural adaptation ( 27 ).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the general pattern underlying the development of psychosis involves the culmination of genetic and environmental factors that may increase (risk factors) or decrease (protective factors) the likelihood of developing psychosis, as well as the interplay between them ( Insel, 2010 ; Radua et al, 2018 ). In this regard, one strand of scientific research is trying to identify, personality traits that can predict both the level of risk and the likelihood of developing the disorder ( Drvaric et al, 2018 ; Meliante et al, 2021 ). Fusar-Poli et al (2014) found anxiety and depression play a central role in psychotic transition whereas, empirical findings on the role of personality are still controversial, and scarcely comprehensive.…”
Section: Introductionmentioning
confidence: 99%
“…Instead, other studies have focused on identifying the most prevalent personality traits in high-risk patients. Studies based on Personality Inventory for DSM-5 (PID-5; Fossati et al, 2013 ) highlighted an additional element to distinguish high-risk patients which are detachment, disinhibition, negative affectivity, and psychoticism ( Drvaric et al, 2018 ; Shi et al, 2018 ; Meliante et al, 2021 ). Drvaric et al (2018) have shown that patients at higher risk for psychosis score higher on two of the five AMPD trait domains – negative affectivity and detachment – than patients at lower risk.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation